Effects of plant protection UAV-based spraying on the vertical distribution of droplet deposition on Japonica rice plants in Northeast China - Cao, Yingli; Yu, Fenghua; Xu, Tongyu; Du, Wen; Guo, Zhonghui; Zhang, Haiyan (International Journal of Agricultural and Biological Engineering, 2021)
In order to study the regularity of the vertical distribution of droplet deposition on rice plants during pesticide spraying operated by a low-flying multi-rotor plant protection unmanned aviation vehicle (UAV), water sensitive spray cards were placed on the leaves at the top, in the middle, and at the bottom of rice plants to acquire data on droplet deposition. In this study, a suspension containing tricylazole and hexaconazole was used in the spraying. The water sensitive spray cards were analyzed by the droplet deposition processing software iDAS to obtain the vertical distribution of the droplets sprayed by the plant protection UAV. The results showed that 1) significant variation was found in the coverage of the droplets in different vertical positions of the rice plants. Within the effective spray width, the best coverage of the droplets was found in the area just below the rotors, whereas the coverage of areas farther away from the rotors was poor. For the different vertical positions of the rice plants, the overall droplet coverage was 58.38% at the top, 33.55% in the middle, and 11.34% at the bottom of the plants; 2) for all vertical positions, the average size of the droplets ranged between 110 μm and 140 μm, which was suitable for the control of plant diseases and insect pests. The highest droplet density was found at the top of the plants, and the distribution of the droplet density was similar in the middle and at the bottom of the rice plants; 3) the diffusion ratio at the top of the rice plants (0.84) was better than that in the middle (0.57) and at the bottom (0.37). The overall relative span could meet the requirements for the actual application. Except for the position in the middle of the plants, the relative span for the other positions of the plants was over 0.67, which is the standard value. This study demonstrated the distribution regularity of droplet deposition along with the vertical direction of rice plants during UAV-based spraying, which is of guiding significance for the use of UAVs in plant protection, the improvement of chemical utilization efficiency, and the reduction of pesticide and fertilizer pollution. Keywords: plant protection UAV, droplet deposition, Japonica rice, droplet size, vertical distribution, spraying, Northeast China DOI: 10.25165/j.ijabe.20211405.5490 Citation: Cao Y L, Yu F H, Xu T Y, Du W, Guo Z H, Zhang H Y. Effects of plant protection UAV-based spraying on the vertical distribution of droplet deposition on Japonica rice plants in Northeast China. Int J Agric & Biol Eng, 2021; 14(5): 27–34.